Subepithelial collagen in intestinal malabsorption - Bossart, R; Henry, K; Booth, C C; Doe, W F (Gut, 1975)
Intestinal biopsies from 146 patients with adult coeliac disease and 13 patients with intestinal villous atrophy of different aetiology were assessed for the presence of subepithelial collagen and compared with a group of 20 control subjects. Subepithelial collagen was a common and non-specific finding observed in intestinal biopsies from patients suffering from adult coeliac disease (36%) and tropical sprue. In adult coeliac disease the described subepithelial changes usually regress following treatment, though marked subepithelial collagen deposition may indicate a poor prognosis. The study showed that the presence of marked subepithelial collagen in a flat jejunal biopsy does not define a separate clinical entity.